Dissociation and Ionization of H+2 by Ultrashort Intense Laser Pulses Probed by Coincidence 3D Momentum Imaging - Ben-Itzhak, I.; Wang, P. Q.; Xia, J. F.; Sayler, A. M.; Smith, M. A.; Carnes, K. D.; Esry, B. D. (My University, 2005)
Laser-induced dissociation and ionization of H+2 were simultaneously measured using coincidence 3D momentum imaging, allowing direct separation of the two processes, even where the fragment kinetic energy is the same for both processes. The results for 45 and 135 fs 790 nm pulses with an intensity of approximately 2.5×1014 W/cm2 differ from each other much more than one would expect from previous measurements with longer pulses. Ionization was negligible for the longer pulse and was strongly aligned along the laser polarization for the shorter pulse, but showed no structure in its kinetic energy distribution. In addition, the ionization to dissociation ratio was found to be much smaller than theoretically predicted for H+2.